Correction: Phylogenetic and histopathological characterization of putative Hepatozoon ophisauri-like lineages in rodents from Italy - Davide Sogliani; Maria Sampieri; Filippo Maria Dini; Mattia Calzolari; Deborah Torri; Valentina Carta; Patrizia Bassi; Alicia Rojas; Giulia Maioli (Acta Parasitologica, 2026)

Phylogenetic and histopathological characterization of putative Hepatozoon ophisauri-like lineages in rodents from Italy - Davide Sogliani; Maria Sampieri; Filippo Maria Dini; Mattia Calzolari; Deborah Torri; Valentina Carta; Patrizia Bassi; Alicia Rojas; Giulia Maioli (Acta Parasitologica, 2026)

Chronostratigraphical ranges of Lower Jurassic larger benthic foraminifera and lithiotid bivalves calibrated by carbon and strontium isotope stratigraphy (Southern Alps, Italy) - Renato Posenato; Davide Bassi; Mariano Parente; Hideko Takayanagi; Anna Cipriani; Claudio Garbelli; Andrea Montanaro; Yoshihiro Asahara; Yasufumi Iryu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The Lower to middle Jurassic of the Maláguide complex (Internal Zones, Betic Cordillera, S Spain) in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga) - Juan C. Braga; Fernando Sola; María José Comas-Rengifo; Davide Bassi (Journal of Iberian Geology, 2025)
The lithostratigraphy, age and paleoenvironmental interpretation of Lower to Middle Jurassic carbonates in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga city) add to the knowledge of the sedimentary evolution of the Maláguide Complex (Internal Zones, Betic Cordillera, southern Spain). In the Barranco de Azagador section in Sierra Cabrera, Sinemurian–Pliensbachian shallow-water carbonates show a mosaic breccia and a hardground at the top. The breccia matrix and the overlying deposits are reddish crinoid packstones with hardgrounds and ammonites late Pliensbachian in age. These features suggest an extensional breakup of an initial carbonate platform giving way to pelagic reduced sedimentation. Three overlying intervals of debris-fall breccias evidence deposition on or at the base of an escarpment. Clasts in the last breccia are Middle Jurassic oolites. In the Cerro de San Antón, shallow-water carbonates change upwards to several intervals of debris-fall breccias with clasts from underlying carbonates and a crinoid packstone matrix. Crinoid packstones with hardgrounds and late Pliensbachian-earliest Toarcian ammonites overlie the breccias. As in the Barranco de Azagador, the disintegration of the pre-late Pliensbachian carbonate platform was followed by pelagic sedimentation on or at the foot of an escarpment. The crinoid packstone is brecciated and covered with a red sandstone that also fills the spaces of laterally equivalent breccias, indicating emersion. Marine sedimentation was regained in the Middle Jurassic with ooid grainstones formed in shoals. The sedimentary evolution of both sections reflects the Pliensbachian rifting phase recognised in other areas of the Maláguide Complex, although the later evolution differs in the two study outcrops.

Success and demise of exceptionally preserved terebratulide brachiopod accumulations in a Jurassic (early Pliensbachian) tropical lagoonal setting (Southern Alps, Italy): brachiopod response to environmental changes - Davide Bassi; Lucia Angiolini; James H. Nebelsick; Renato Posenato (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Paleoenvironmental significance of growth story of long-living deep-water acervulinid macroids from Kikai-jima shelf, Central Ryukyu Islands, Japan - Davide Bassi; Juan Carlos Braga; Ryuji Asami; Kazuhisa Goto; Sönke Szidat; Hideko Takayanagi; Yasufumi Iryu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Biogeographical patterns of the porcelaneous larger foraminifer Alveolinella quoyi through the integration of fossil data - Davide Bassi; Yasufumi Iryu; Johannes Pignatti; Kazuhiko Fujita; Willem Renema (Geobios, 2024)

Porcelaneous larger foraminiferal responses to Oligocene–Miocene global changes - Davide Bassi; Juan Carlos Braga; Johannes Pignatti; Kazuhiko Fujita; James H. Nebelsick; Willem Renema; Yasufumi Iryu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A new species of the larger porcelaneous foraminifer Borelis provides novel insights into Neogene to Recent western Pacific palaeobiogeographical dispersal patterns - Davide Bassi; Yasufumi Iryu; Shunichi Kinoshita; Kazuhiko Fujita; Johannes Pignatti (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Multi‐approach characterization of shallow‐water carbonates off Minamitorishima and their depositional settings/history - Md. Aftabuzzaman; Kazuki Yomogida; Shota Suzuki; Hideko Takayanagi; Akimasa Ishigaki; Shiki Machida; Yoshihiro Asahara; Koshi Yamamoto; Naoto Hirano; Shin‐Ichi Sano; Shun Chiyonobu; Davide Bassi; et al. (Island Arc, 2021)
Sedimentological, geochemical, and chronological analyses were carried out on 18 carbonate rock samples collected at depths of 938, 1085, and 3354 m on the western slope of Minamitorishima (Marcus Island), which is located near the western margin of the Pacific Plate. Four groups of carbonate rocks were distinguished: a mollusk‐rich limestone, a coral‐rich dolomite, a foraminiferal‐nannofossil packstone, and a phosphatized mudstone/wackestone. The mollusk‐rich limestone is characterized by the dominance of bivalves (including rudists) and gastropod shells. Strontium isotope ratios ( 87 Sr/ 86 Sr) and Mesorbitolina ex gr. texana (a large benthic foraminifer) indicate that the shallow‐water carbonates were deposited during the late Aptian–early Albian (ca. 123–111 Ma). The coral‐rich dolomite is characterized by abundant scleractinian corals and nongeniculate coralline algae associated with encrusting acervulinid foraminifers. The biotic composition is similar to that of the Oligocene–Pleistocene carbonates reported from other seamounts in the northwestern Pacific. Geochemical data show that the coral‐rich carbonates were dolomitized at 9.5–6.8 Ma (Tortonian–Messinian) and that normal seawater was the most likely parent fluid. The foraminiferal‐nannofossil packstone is a semi‐consolidated foraminiferal‐nannofossil ooze and was deposited during the Pleistocene (0.99–0.45 Ma). The phosphatized mudstone/wackestone is marked by the absence of macrofossils and the presence of traces of planktic foraminifers. Although its depositional age is not constrained, the Sr isotope ratios indicate that the phosphatization occurred at 33.2–28.9 Ma. After the deposition of the Cretaceous shallow‐water carbonates, including the mollusk‐rich limestone, Minamitorishima was drowned and its top was covered with a pelagic cap, represented by the mudstone/wackestone. The late Eocene–early Oligocene volcanism (40.2–33.2 Ma) caused episodic uplift and returned the top of Minamitorishima to a shallow‐water environment. After the early Oligocene phosphatization of the pelagic cap, coral reefs flourished on the top of this island. The reef limestone was dolomitized during the Tortonian–Messinian.

High‐resolution upper Pliocene to Pleistocene calcareous nannofossil biostratigraphy in Ocean Drilling Program Hole 1146A in the South China Sea - Sara Emanuel; Tokiyuki Sato; Shun Chiyonobu; J. Bruce H. Shyu; Davide Bassi; Yasufumi Iryu (Island Arc, 2021)
We established a high‐resolution calcareous nannofossil biostratigraphy for the late Pliocene–Pleistocene by analyzing a 242 m‐thick, continuous sedimentary succession from Ocean Drilling Program Site 1146, Hole A, in the South China Sea (SCS). A total of 14 calcareous nannofossil datums were detected in the SCS succession. They are, in descending order: first occurrence (FO) of Emiliania huxleyi , last occurrence (LO) of Pseudoemiliania lacunosa , LO of Reticulofenestra asanoi , FO of Gephyrocapsa parallela , FO of R. asanoi , LO of large Gephyrocapsa spp., FO of large G . spp., FO of Gephyrocapsa oceanica , FO of Gephyrocapsa caribbeanica , LO of Calcidiscus macintyrei , LO of Discoaster brouweri , LO of Discoaster pentaradiatus , LO of Discoaster surculus , and LO of Discoaster tamalis . The FO of E. huxleyi was not precisely detected due to poor preservation and dissolution of nannofossils in the underlying strata. We refined the previous calcareous nannofossil biostratigraphy in the SCS by identifying Gephyrocapsa species and four evolutionary extinction events of the genus Discoaster . The proposed calcareous nannofossil biostratigraphy correlates with those reported in other terrestrial and marine areas/sites and global benthic foraminiferal δ 18 O records. The age–depth curves based on nannofossil biostratigraphy indicate a significant increase in the sedimentation rates at the LO of R. asanoi (0.91–0.85 Ma). The timing of this increase corresponds to reef expansion in the Ryukyu Islands linked to a stepwise increase in Kuroshio Current intensity. This timing is broadly coeval with a sea surface temperature increase of ∼2 °C in the northwestern Pacific due to expansion of the Western Pacific Warm Pool towards the north and south subtropical regions. This can be explained by increased weathering and erosion of terrestrial areas in glacial periods and increased rainfall causing higher sediment transport in interglacial periods, which were both linked to Middle Pleistocene Transition‐related climatic changes.

Species interactions and climate change: How the disruption of species co‐occurrence will impact on an avian forest guild - Mattia Brambilla; Davide Scridel; Gaia Bazzi; Luca Ilahiane; Aaron Iemma; Paolo Pedrini; Enrico Bassi; Radames Bionda; Luigi Marchesi; Fulvio Genero; Norbert Teufelbauer; Remo Probst; et al. (Global Change Biology, 2020)
Interspecific interactions are crucial in determining species occurrence and community assembly. Understanding these interactions is thus essential for correctly predicting species' responses to climate change. We focussed on an avian forest guild of four hole‐nesting species with differing sensitivities to climate that show a range of well‐understood reciprocal interactions, including facilitation, competition and predation. We modelled the potential distributions of black woodpecker and boreal, tawny and Ural owl, and tested whether the spatial patterns of the more widespread species (excluding Ural owl) were shaped by interspecific interactions. We then modelled the potential future distributions of all four species, evaluating how the predicted changes will alter the overlap between the species' ranges, and hence the spatial outcomes of interactions. Forest cover/type and climate were important determinants of habitat suitability for all species. Field data analysed with N‐mixture models revealed effects of interspecific interactions on current species abundance, especially in boreal owl (positive effects of black woodpecker, negative effects of tawny owl). Climate change will impact the assemblage both at species and guild levels, as the potential area of range overlap, relevant for species interactions, will change in both proportion and extent in the future. Boreal owl, the most climate‐sensitive species in the guild, will retreat, and the range overlap with its main predator, tawny owl, will increase in the remaining suitable area: climate change will thus impact on boreal owl both directly and indirectly. Climate change will cause the geographical alteration or disruption of species interaction networks, with different consequences for the species belonging to the guild and a likely spatial increase of competition and/or intraguild predation. Our work shows significant interactions and important potential changes in the overlap of areas suitable for the interacting species, which reinforce the importance of including relevant biotic interactions in predictive climate change models for increasing forecast accuracy.

Recent progress in study on calcareous algae and algal sediments - Yasufumi Iryu; Davide Bassi (Island Arc, 2017)

The emerging role of Acid Sphingomyelinase in autophagy - Cristiana Perrotta; Davide Cervia; Clara De Palma; Emma Assi; Paolo Pellegrino; Maria Teresa Bassi; Emilio Clementi (Apoptosis, 2015)

Tracking paleoenvironmental changes in coralline algal-dominated carbonates of the Lower Oligocene Calcareniti di Castelgomberto formation (Monti Berici, Italy) - James H. Nebelsick; Davide Bassi; Julia Lempp (Facies, 2013)

Origin and resedimentation of rhodoliths in the Late Paleocene flysch of the Polish Outer Carpathians - Stanisław Leszczyński; Bogusław Kołodziej; Davide Bassi; Ewa Malata; M. Adam Gasiński (Facies, 2012)

An Upper Miocene siliciclastic-carbonate ramp: depositional architecture, facies distribution, and diagenetic history (Capo Vaticano area, southern Italy) - Pierparide Gramigna; Davide Bassi; Franco Russo (Facies, 2012)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Upper Eocene larger foraminiferal–coralline algal facies from the Klokova Mountain (southern continental Greece) - Filippo Barattolo; Davide Bassi; Roberta Romano (Facies, 2007)

Coralline red algal assemblage from the Middle Pliocene shallow-water temperate carbonates of the Monte Cetona (Northern Apennines, Italy) - Alessio Checconi; Davide Bassi; Leonsevero Passeri; Roberto Rettori (Facies, 2007)

Photosynthesis research in Italy: a review - Giorgio Forti; Angela Agostiano; Roberto Barbato; Roberto Bassi; Enrico Brugnoli; Giovanni Finazzi; Flavio M. Garlaschi; Robert C. Jennings; Bruno Andrea Melandri; Massimo Trotta; Giovanni Venturoli; Giuliana Zanetti; et al. (Photosynthesis Research, 2006)

Facies dynamics in Eocene to Oligocene circumalpine carbonates - James H. Nebelsick; Michael W. Rasser; Davide Bassi (Facies, 2005)

Recovery of carbonate platform production in the Lombardy Basin during the Anisian: paleoecological significance and constrain on paleogeographic evolution - Fabrizio Berra; Roberto Rettori; Davide Bassi (Facies, 2005)

Microfacies analysis and palaeoenvironmental interpretation of Lower Oligocene, shallow-water carbonates (Gornji Grad Beds, Slovenia) - James H. Nebelsick; Davide Bassi; Katica Drobne (Facies, 2000)

Coralline algal facies and their palaeoenvironments in the Late Eocene of Northern Italy (Calcare di Nago, Trento) - Davide Bassi (Facies, 1998)